Gaseous acids in the atmosphere at Syowa Station, Antarctica (abstract) - Kanamori, Nobuko; Kanamori, Satoru; Nishikawa, Masataka; Watanabe, Okitsugu (National Institute of Polar Research, 1993)
P(論文) Seasonal variation of atmospheric aerosols and gaseous acids in the atmosphere at Syowa Station was observed during JARE-31 by the use of a 3-stage air filter unit which consists of an 0.4 departmental bulletin paper